A Pathway to Clinician-Led Culture Change in the Operating Theatre. Issue 6 (June 2016) - Gibbs, J; Smith, P
Noise in the operating theatre environment has remained a persistent and unresolved problem (Szalma & Hancock 2011). The problem currently lacks an effective solution (Schafer et al 2012). In order to partially resolve this issue, the authors created a behavioural noise reduction tool called 'Below Ten Thousand'. This study identifies a potential solution to the problem of behavioural noise in the operating theatre, and indicates further research must be undertaken to identify the full scale of benefits this technique can deliver to the team environment in the operating theatre.